The Influence of Job Satisfaction on Psychological Well-Being of Early Childhood Teachers - Ni Made Puja Pramana Devi; Sri Kurnianingsih (Universitas Katolik Soegijapranata, 2025)
The role of teachers is crucial in shaping children's character and development, especially at the Early Childhood Education (PAUD) level. However, working as a early childhood teacher often comes with various challenges that can affect their psychological well-being. This decline in psychological well-being can have an impact on motivation, performance, and the quality of teachers' interactions with their students. This study aims to determine the effect of job satisfaction on the psychological well-being of Early childhood teachers in Surakarta. The research method used is quantitative. The sample consisted of 117 active Early childhood teachers in Pasar Kliwon and Serengan districts of Surakarta City. Data collection was conducted using the Ryff Psychological Well-Being Scale (PWBS) to measure psychological well-being and the Job Satisfaction Survey (JSS) Scale Spector to measure job satisfaction. The analysis results showed that the regression model was statistically significant overall, F(1,115)= 142.01, p= .000, with R²= .553. Job satisfaction significantly predict psychological well-being, β= 0.265, p= .000.